Evaluating the Impact of a Proactive Chat Feature on Reference Questions, Their Complexity and Subject Matter. - Hervieux, Sandy (Internet Reference Services Quarterly)
This study aims to investigate the impact of a proactive chat widget on the types of questions received and their complexity at the McGill University Libraries. A qualitative analysis of the proactive chat transcripts using coding for types and subject of questions as well as READ scale level was used in addition to a quantitative analysis of the pages where users accessed the proactive chat feature. The author determined that including a proactive chat feature on webpages related to research topics significantly increased the number of reference interactions as well as the complexity level of the questions asked by patrons. She also identified that questions related to law were the most common on proactive chat and that the pop-up on the law research guide was the most used which indicates that users received point-of-need help related to this topic. This is the first study to investigate the link between placing a proactive chat widget on research related pages and the increase in reference questions. Similarly, it is one of the few studies identifying the main referral pages for proactive chat and how it impacts the subjects of the questions received.